Studi Eksplorasi Literasi Halal dan Sertifikasi Halal Pelaku Usaha UMKM di Lenteng Kabupaten Sumenep - Himmah, Azizatul; Qadariyah, S.H.I., M.E.I, Lailatul; Sarkawi SHI, M.pd I (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2024)
In Islam, consuming food and drinks is very concerned about its halalness. Because all aspects of life, be it worship, economy, culture, have been regulated in the Qur'an, hadith, and itihad (agreement of scholars). The certification that has been provided by BPJPH is a process of ensuring that food products, medicines and others that will be consumed are in accordance with halal standards and sharia that have been regulated in Islam. However, considering that there are still many MSME business actors who have not carried out halal certification on their products due to several things, one of which is unfamiliarity with the process of applying for halal certification, this study aims to provide understanding and knowledge related to halal literacy to several MSME players in Lenteng village, Sumenep Regency so that they can understand the importance of halal certification for their products. Descriptive qualitative research techniques are used in this research method. The data used in this study are primary data derived from observations, interviews with MSME actors, and documentation and secondary data derived from data obtained from literature studies such as books, journals, and available report documents.